Extractive Industries and Indigenous Peoples: A Bibliometric Analysis (2006-2026) - Cornelia Novita Verawati Tanesib; Hartuti Purnaweni; Rully Rahadian (Lembaga Teewan Journal Solutions, 2026)
This study aims to map the intellectual structure, thematic evolution, and research trends on extractive industries and indigenous peoples. Using a bibliometric approach, 1,186 Scopus-indexed publications published between 2006 and 2026 were analyzed through Bibliometrix and Biblioshiny in RStudio. The analysis included publication performance, citation analysis, keyword co-occurrence, thematic mapping, thematic evolution, and topic trend analysis. The results reveal a 288% increase in publication output over the study period, indicating growing scholarly attention to the topic. Research production remains concentrated in Global North countries, particularly the United States (28.08%), Canada (21.67%), and Australia (13.15%). Keyword analysis identified mining (205 occurrences), indigenous peoples (195), and environmental justice (72) as the dominant themes, while recent trends highlight increasing attention to critical minerals, lithium mining, and the green energy transition. The findings suggest that governance remains central yet underdeveloped in addressing extractive conflicts involving indigenous communities. This study contributes a comprehensive overview of the field and identifies emerging directions for future research and policy development.